Exploring Central Vascular Anatomy With Axial Computed Tomography During Surgery for Sigmoid Colon and Rectal Cancer: New Insights Into the Anatomical Relationship Between the Inferior Mesenteric Artery and the Duodenum - Cheng, Zhiqiang; Ren, Pengfei; Wang, Xiaoyan; Wang, Kexin; Yan, Zhibo; Bi, Dongsong; Wang, Yanlei; Dai, Yong; Zhang, Xiang (Frontiers in Surgery, 2021)
Background: In some individuals, the inferior mesenteric artery (IMA) originates from the aorta above the lower edge of the duodenum. This anatomical feature has rarely been reported but may be important in guiding central vascular ligation and lymph node dissection in colorectal surgery. This retrospective study aimed to explore the anatomical relationship between the IMA and the duodenum and evaluate its potential impact on the efficacy of D3 lymph node dissection. Methods: A total of 439 patients undergoing laparoscopic colorectal surgery at the Department of General Surgery, Qilu Hospital of Shandong University, were retrospectively enrolled. Clinical data from axial computed tomography (CT) scans were collected and analysed. Results: In 27.69% of patients, the IMA originated at or above the lower edge of the duodenum (median distance: -8 mm). These patients were characterised by a shorter superior mesenteric artery to aortic bifurcation distance, a superiorly located IMA origin, and a greater distance between the IMA and both the left colic artery and the inferior mesenteric vein. The number of harvested lymph nodes was not significantly associated with the distance between the IMA and the duodenum (P=0.858). Conclusions: Preoperative axial CT scans can provide a great deal of information regarding central vascular anatomy in the context of sigmoid colon and rectal cancer surgery. Nearly one-third of patients have the IMA originating at or above the duodenum. Whether this anatomical feature affects D3 lymph node dissection warrants further investigation.